Examining playground engagement between elementary school children with and without autism spectrum disorder. (August 2016) - Locke, Jill; Shih, Wendy; Kretzmann, Mark; Kasari, Connie
Little is known about the social behavior of children with and without autism spectrum disorder during recess. This study documented the naturally occurring recess engagement and peer interaction behaviors of children with and without autism spectrum disorder in inclusive school settings. Participants included 51 children with autism spectrum disorder and 51 classmates without autism spectrum disorder who served as peer models matched on gender, classroom, grade, age, and ethnicity. Using a timed-interval behavior-coding system, children with autism spectrum disorder spent approximately 30% of their recess time engaged in solitary activities, whereas their classmates only spent approximately 9% of recess unengaged. In addition, children with autism spectrum disorder spent about 40% of the recess period jointly engaged with peers in a reciprocal activity, conversation, or game as compared to 70% for matched classmates. These findings provide a context for which to interpret intervention outcomes and gains for children with autism spectrum disorder in inclusive settings.